2022
DOI: 10.3390/medicina58121811
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study about Knowledge, Attitude, and Practices among Primary Health Care Physicians in Jazan Province, Saudi Arabia, Regarding Rome IV Criteria for Diagnosis of Irritable Bowel Syndrome

Abstract: Background and objectives: Most individuals with irritable bowel syndrome (IBS) are diagnosed by primary health care (PHC) physicians. However, a significant percentage of patients remain undiagnosed or misdiagnosed owing to the lack of knowledge or a systematic strategy regarding the use of ROME IV criteria for the diagnosis of IBS. Thus, in this study, we aimed to assess the knowledge, attitude, and practices among primary health care physicians in Jazan Province, Saudi Arabia, regarding ROME IV criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Participants with less than three years of experience were the most frequent (n = 312, 50.1%). The age and gender in our study were on the same line as reported in Hungin et al's study [ 21 ], and the studied general practitioners were predominant in some other studies as in Abusageah et al's study [ 8 ], which supported our findings.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Participants with less than three years of experience were the most frequent (n = 312, 50.1%). The age and gender in our study were on the same line as reported in Hungin et al's study [ 21 ], and the studied general practitioners were predominant in some other studies as in Abusageah et al's study [ 8 ], which supported our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Given the high prevalence of IBS in Saudi Arabia, there is limited information on doctors' attitudes and awareness of the illness [ 8 ]. Therefore, this study aimed to assess the self-reported knowledge, attitudes, and practices related to the Rome IV criteria for diagnosing IBS among PHC physicians in various regions and cities of Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations